PENGARUH PUPUK BAKTERI FOTOSINTESIS DAN SISTEM PULL–PUSH TERHADAP PERTUMBUHAN DAN HASIL JAGUNG (Zea mays L.) - Panunggul, Victor Bintang; Sitanini, Ayu; Arimurti Susanto, Niken Hapsari; Abidin, Zaenal (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2025)
This study aims to determine the impact of photosynthetic bacterial fertilizer and the pull-push cultivation technique on corn. The research was conducted in Banjaran Village, Purbalingga Regency. The experimental design used was a completely randomized block design. The treatments for photosynthetic bacteria included S0 (control), S1 (50 mL/2L), and S2 (100 mL/2L), as well as the pull-push system treatments P0 (control), P1 (lemongrass), and P2 (groundnut). Each treatment was replicated three times and analyzed using ANOVA. Duncan's Multiple Range Test (DMRT) (α=5%) was employed for significantly different results. The observed variables were plant height, number of leaves, dry root weight, dry plant weight, and total chlorophyll. The results indicated that the application of photosynthetic bacterial fertilizer increased plant height but did not affect the number of leaves. The pull-push cultivation technique showed significance in the lemongrass treatment and total chlorophyll, while no interaction was observed between the two applied treatments.